Analisis Pelaksanaan Pembelajaran Pendidikan Jasmani pada Masa Pandemi Covid-19 di Sekolah Dasar Negeri di Kecamatan Warureja Kabupaten Tegal - almafdi, juang inves; Wahyudi, Agung (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine the planning, implementation, and evaluation of physical education learning during the COVID-19 pandemic at Public Elementary Schools in Warureja District, Tegal Regency in 2022. This research method was qualitative descriptive, using a survey method. Data collection techniques through observation, interviews, and documentation. The sample of this research is SD Negeri in Warureja District. The results of this study indicate that the implementation of physical education learning during the COVID-19 pandemic at Public Elementary Schools in Warureja District has been carried out face-to-face 100%. Starting from the planning, implementation and evaluation of physical education learning goes well according to the applicable curriculum and the implementation rules of Limited PTM. The results of the study concluded, 1) Learning planning was in accordance with the curriculum and rules of Limited PTM, 2) Physical education learning had been carried out face-to-face and went well, 3) Learning Evaluation had better progress, 4) Obstacles during the implementation of learning Physical education online has begun to be overcome with the implementation of face-to-face physical education learning.